Paradoxical Leadership and Employee Task Performance: A Sense-Making Perspective - Zhang, Wei; Liao, Shudi; Liao, Jianqiao; Zheng, Quanfang (Frontiers in Psychology, 2021)
Paradoxical leadership has received increasing research attention in recent years. Yet, questions remain as to why and when paradoxical leadership is effective in promoting employee work outcomes. Drawing upon the sense-making perspective, we propose that paradoxical leadership enhances employee task performance by increasing employees’ adaptability, and paradoxical leadership is more effective when employees have higher levels of Zhong Yong thinking and organizational identification. To test our hypotheses, we conducted a multi-source and multi-wave survey study among 235 employees and their supervisors in southern China. The results of the regression analyses fully support our hypotheses. In general, our findings shed light on the underlying mechanisms, as well as the boundary conditions, of the effect of paradoxical leadership. The theoretical and practical implications of these findings are discussed.